MODERASI BERAGAMA DALAM PANDANGAN ABDULRAHMAN WAHID (GUS DUR) DAN MUHAMMAD JUSUF KALLA DALAM PERSPEKTIF KEBHINEKAAN - Deri Saputra; Andarweni Astuti (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2022)
This paper discusses the views of Abdulrahman Wahid (Gus Dur), Muhammad Jusuf Kalla, and . regarding the concept of religious moderation in the perspective of Pluralism, Ideology (Pancasila), and in Education. This paper departs from the interpretation of religious texts that need to be traced socio-historically into scientific literature that can be used as a synthesis of religious moderation in Indonesia. To find out their views on the concept of religious moderation, the authors use a literature study approach obtained from journals and books related to the concept of moderation from the three figures above. The results of this study conclude that first, the perspective of Abdulrahman Wahid (Gus Dur) is religious moderation as a conception that can build tolerance and harmony in order to strengthen national unity and integrity. Second, the perspective of Muhammad Jusuf Kalla that religious moderation must begin with a sense of brotherhood, both brotherhood between religious communities, brotherhood in the nation and state, as well as brotherhood between fellow human beings and mutual respect in the sense of giving freedom in carrying out their respective worship, not mutually exclusive. insulting so that unwanted violence does not arise in religion